Introducing the new BTS Guideline: Management of non-tuberculous mycobacterial pulmonary disease (NTM-PD). Issue 11 (20th October 2017) - Haworth, Charles S; Floto, R Andres
Abstract : The new BTS Guidelines for the management of non-tuberculous mycobacterial pulmonary disease combine the best available evidence with expert consensus to generate a set of pragmatic Guidelines, published as a supplement to this issue of Thorax, to assist in the management of these challenging infections.